The change in temperature during Lena's sleepover was 6°F. It can therefore be said that the temperature rose by 6°F during the sleepover.
To find the change in temperature, subtract the initial temperature from the final temperature, in other words, Subtract the temperature on Friday night from the temperature on Saturday morning.
Change in temperature = Final temperature - Initial temperature
Change in temperature = (−1°F) - (−7°F)
Change in temperature = −1 + 7
Change in temperature = 6°F
So, the temperature rose by 6°F during the sleepover.
Find more exercises on temperature change;
#SPJ3
Answer:
6F
Step-by-step explanation:
B. y = x2 − 5 y = −x − 1
C. y = x2 + 5 y = −x + 1
D. y = x2 + 5 y = −x − 1
Answer:
Option (A)
Step-by-step explanation:
For equation of the line,
Let the equation is, y = mx + b
Slope 'm' of the line passing through two points (-3, 4) and (2, -1),
m =
=
= -1
y-intercept of this line, b = 1
Now we substitute these values in the equation,
y = -x + 1
Let the equation of the parabola is,
y = a(x - h)² + k
Here, (h, k) is the vertex of the parabola,
Since vertex of the given parabola is (0, -5),
then the equation will be,
y = a(x - 0)²- 5
y = ax² - 5
Since a point (2, -1) lies on this parabola,
-1 = a(2)² - 5
5 - 1 = 4a
a = 1
Equation of the parabola will be,
y = x² - 5
Therefore, Option (A) will be the answer.
Answer:
There are 1600 residents.
Step-by-step explanation:
0.2 times x = 320 divide by 0.2
x = 1600
Answer:
65
Step-by-step explanation:
I think. hope this hepls
D
The model involves similar triangles with the ratios of corresponding sides being equal
let x be the length of the tree's shadow, then
= ( cross- multiply )
15x = 11 × 28
Answer:
D
Step-by-step explanation:
i went to K12
Answer:
x= -2
Step-by-step explanation: (remember the 6 in this equation is positive so you'll subtract it and the 2 is actually -2x. First, you'll subtract 6 from itself and 10, the two 6's cancel out and 10-6=4. Then, you'll divide -2 and 4 by -2, the two -2's cancel out and 4 divided by -2 is -2. Finally, you'll see that x = -2. This is all done by the order of operations also known as PEMDAS. )
6 - 2x =10
-6 -6
-----------------
-2x = 4
------------
-2 = -2
x = -2